PERLINDUNGAN HUKUM TERHADAP SAKSI DAN KORBAN KEJAHATAN DALAM PROSES PERADILAN PIDANA DI INDONESIA - Rini Retno Winarni (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2011)
There are many articles of KUHAP (Criminal Law of Procedure) which regulates the protection of criminal causes less for the protection of victim actually, the equal protection for witness (victim) as the adagium said "Equality before the law". The minimum of the protection for witness and victim, shows the witness and victim who appears witness criminal litigation process has the protection automatically as mention in the criminal law of procedure. The handicap factors are : The regulation, the legend awareness, the support facility and the human resources.